2009
DOI: 10.1111/j.1095-8312.2009.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical connections between the Maghreb and the Mediterranean peninsulas of southern Europe

Abstract: The glacial-interglacial cycles have caused severe range modifications of species' distributions. In Europe, thermophilic species had to retreat into geographically distinct southern refugia during glaciations. This process produced strong genetic imprints, which are still detectable by the present pattern of genetic differentiation and the distribution of regional diversity. To reveal the biogeographical imprints in the western Mediterranean, we analysed 26 populations of the butterfly Maniola jurtina spread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 51 publications
5
52
0
Order By: Relevance
“…africana (Romo and Boratyński 2007), found also at the genetic level using the RAPD and AFLP method (Jiménez et al 2003;Terrab et al 2008, respectively). Similar dependences have been found also in Abies species on the chloroplast DNA (Terrab et al 2007), and other organisms (for review see Weiss and Ferrand, 2007;Terrab et al 2008;Habel et al 2009 andOrtiz et al 2009). …”
Section: Geographical and Ecological Remarkssupporting
confidence: 75%
See 2 more Smart Citations
“…africana (Romo and Boratyński 2007), found also at the genetic level using the RAPD and AFLP method (Jiménez et al 2003;Terrab et al 2008, respectively). Similar dependences have been found also in Abies species on the chloroplast DNA (Terrab et al 2007), and other organisms (for review see Weiss and Ferrand, 2007;Terrab et al 2008;Habel et al 2009 andOrtiz et al 2009). …”
Section: Geographical and Ecological Remarkssupporting
confidence: 75%
“…Of particularly high influence was the Messinian Salinity Crisis, resulting in the connection of Europe and Africa (Krijgsman et al 1999;Schneck et al 2010;Jaromilo-Correa et al 2010). The link between Eurasian and African tectonic plates was coincident with an extremely dry climate, but served as an intercontinental pathway between both sides of the Mediterranean (Krijgsman et al 1999;Thompson 2005;Habel et al 2009;Schneck et al 2010). The separation of the Iberian Peninsula from Africa by the opening of the Strait of Gibraltar at the turn of the Miocene/Pliocene about 5 Myr BP (Krijgsman et al 1999) has likely created an impermeable barrier for plant migration (Terrab et al 2007(Terrab et al , 2008Habel et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, such an extensive barrier to dispersal of biota may cause the differentiation of assemblages by limiting colonization across the barrier, and by facilitating speciation of isolated populations. Several studies confirmed speciation processes across the Strait of Gibraltar in multiple taxa, although the frequency of this phenomenon is greatly dependent on the dispersal abilities of each taxon; flying species, and those that tolerate salt water, tend to show lower levels of differentiation across the Strait (Habel et al 2009). Existing information is still insufficient to make broad generalizations about the level of permeability of the Strait for birds, but evidence indicates that it is lower in forest-adapted birds than in arid-adapted species .…”
Section: Introductionmentioning
confidence: 94%
“…Comparable conditions persisted even during the Pleistocene glacial periods and in fact southern Iberia and the adjacent areas of North Africa have been classically merged in the same glacial refuge, the Atlantic-Mediterranean centre (De Lattin 1949). In the case of birds, as in that of other flying organisms (Habel et al 2009), the Mediterranean remained a relatively permeable barrier, which partly prevented local differentiation processes and facilitated the homogenisation of the assemblages during this period.…”
Section: Guild Assemblagementioning
confidence: 99%